An Analysis of Students' Learning Difficulties in Studying the Quran and Hadith - Indriani, Ria (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2025)
Learning Al-Qur'an and Hadith is a fundamental component of Islamic education, as it plays a pivotal role in shaping students' cognitive, affective, and psychomotor competencies. However, its implementation in madrasas continues to face various challenges that affect the overall quality of learning. This study aims to identify the types of difficulties students experience in learning Al-Qur'an and Hadith at MTsN 3 Palu City, analyze the contributing factors, and formulate strategic recommendations to enhance learning quality. Employing a descriptive qualitative approach, data were collected through participatory observation, in-depth interviews, and document analysis. The findings reveal three major categories of learning difficulties. In the cognitive domain, students encounter significant challenges in understanding tajwīd rules, comprehending the meaning of hadiths, and grasping the historical context of verses and prophetic traditions. In the affective domain, low intrinsic motivation and a weak appreciation of Qur'anic values are evident. In the psychomotor domain, many students are unable to recite the Qur'an accurately (tartīl) and face difficulties in memorizing and applying religious teachings in daily life. The primary contributing factors include varying levels of Arabic proficiency, the predominance of lecture-based teaching methods, limited learning facilities, and the multicultural environment of Palu City. This study underscores the need for more varied, contextualized, and adaptive learning approaches, enhanced teacher competence, and improved learning infrastructure. The findings are expected to provide valuable insights for madrasas seeking to improve the holistic effectiveness of Al-Qur'an and Hadith learning. Abstrak: Belajar Al-Qur'an dan Hadits merupakan komponen fundamental dalam pendidikan Islam, karena berperan penting dalam membentuk kompetensi kognitif, afektif, dan psikomotorik siswa. Namun, implementasinya di madrasah masih menghadapi berbagai tantangan yang memengaruhi kualitas pembelajaran secara keseluruhan. Penelitian ini bertujuan untuk mengidentifikasi jenis-jenis kesulitan yang dialami siswa dalam mempelajari Al-Qur'an dan Hadits di MTsN 3 Kota Palu, menganalisis faktor-faktor yang berkontribusi, dan merumuskan rekomendasi strategis untuk meningkatkan kualitas pembelajaran. Dengan menggunakan pendekatan kualitatif deskriptif, data dikumpulkan melalui observasi partisipatif, wawancara mendalam, dan dokumentasi. Temuan menunjukkan tiga kategori utama masalah pembelajaran. Di domain kognitif, siswa mengalami kesulitan signifikan dalam memahami aturan tajwid, makna hadits, dan konteks historis ayat-ayat Al-Qur'an serta tradisi nabawi. Di domain afektif, motivasi intrinsik yang rendah dan apresiasi yang lemah terhadap nilai-nilai Al-Qur'an terlihat jelas. Di domain psikomotorik, banyak siswa belum mampu membaca Al-Qur'an dengan benar (tartīl) dan menghadapi hambatan dalam menghafal serta menerapkan ajaran agama dalam kehidupan sehari-hari. Faktor-faktor utama yang berkontribusi meliputi tingkat kemahiran bahasa Arab yang bervariasi, dominasi metode pengajaran berbasis ceramah, fasilitas pembelajaran yang terbatas, dan lingkungan multikultural Kota Palu. Studi ini menyoroti pentingnya pendekatan pembelajaran yang lebih beragam, kontekstual, dan adaptif, peningkatan kompetensi guru, serta perbaikan infrastruktur pembelajaran. Temuan ini diharapkan dapat menjadi acuan berharga bagi madrasah dalam meningkatkan efektivitas holistik pengajaran Al-Qur'an dan Hadits.